Facilities planning - Tompkins, James A (Hoboken, NJ : John Wiley and Sons, 2010)
"When it comes to facilities planning, engineers turn to this book to explore the most current practices. The new edition continues to guide them through each step in the planning process. The updated material includes more discussions on economics, the supply chain, and ports of entry. It takes a more global perspective while incorporating new case studies to show how the information is applied in the field. Many of the chapters have been streamlined as well to focus on the most relevant topics. All of this will help engineers approach facilities planning with creativity and precision."--BOOK JACKET
Part One DEFINING REQUIREMENTS. Chapter One INTRODUCTION. 1.1 Facilities Planning Defined. 1.2 Significance of Facilities Planning. 1.3 Objectives of Facilities Planning. 1.4 Facilities Planning Process. 1.5 Strategic Facilities Planning. 1.6 Developing Facilities Planning Strategies. 1.7 Examples of Inadequate Planning. 1.8 Summary. References. Problems. Chapter Two PRODUCT, PROCESS, AND SCHEDULE DESIGN. 2.1 Introduction. 2.2 Product Design. 2.3 Process Design. 2.4 Schedule Design. 2.5 Facilities Design. 2.6 Summary. References. Problems. Chapter Three FLOW SYSTEMS, ACTIVITY RELATIONSHIPS, AND SPACE REQUIREMENTS. 3.1 Introduction. 3.2 Flow Systems. 3.3 Material Flow System. 3.4 Departmental Planning. 3.5 Activity Relationships. 3.6 Space Requirements. 3.7 Summary. References. Problems. Chapter Four PERSONNEL REQUIREMENTS. 4.1 Introduction. t
Includes bibliographical references and index
Keywords: Factories -- Design and construction; Facility management; Industrial engineering